2017
DOI: 10.1002/eat.22764
|View full text |Cite
|
Sign up to set email alerts
|

Dorsomedial prefrontal cortex repetitive transcranial magnetic stimulation treatment of posttraumatic stress disorder in eating disorders: An open‐label case series

Abstract: Posttraumatic stress disorder (PTSD) is a common comorbid condition in anorexia nervosa (AN) and bulimia nervosa (BN), and may be associated with reduced response to treatment. We report on a case series employing repetitive transcranial magnetic stimulation (rTMS) with a novel target, the dorsomedial prefrontal cortex (DMPFC). Fourteen subjects with eating disorders and comorbid PTSD received 20-30 neuronavigated DMPFC-rTMS treatments on an open-label basis. PTSD symptoms were assessed pretreatment and posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…With this rationale, several studies evaluated the feasibility and the clinical benefits of using TMS or tDCS alone or combined with psychotherapy. In this review, we evaluated 13 RCTs [9,10,18,[21][22][23][24][25][26][27][28][29][30], 11 case series [8,[31][32][33][34][35][36][37][38][39][40], and 6 case reports [7,21,[41][42][43][44] on neuromodulation for PTSD, focusing on TMS, tDCS, and DBS. Details of the articles pooled for analysis in our review are summarized in Tables 1 (TMS), 2 (tDCS), and 3 (DBS).…”
Section: Resultsmentioning
confidence: 99%
“…With this rationale, several studies evaluated the feasibility and the clinical benefits of using TMS or tDCS alone or combined with psychotherapy. In this review, we evaluated 13 RCTs [9,10,18,[21][22][23][24][25][26][27][28][29][30], 11 case series [8,[31][32][33][34][35][36][37][38][39][40], and 6 case reports [7,21,[41][42][43][44] on neuromodulation for PTSD, focusing on TMS, tDCS, and DBS. Details of the articles pooled for analysis in our review are summarized in Tables 1 (TMS), 2 (tDCS), and 3 (DBS).…”
Section: Resultsmentioning
confidence: 99%
“…In other study, patients with AN (restrictive and binge-purge subtypes), BN, and EDNOS were included. 37 In this study, 20–30 sessions of rTMS were applied to the bilateral DMPFC, and all patients suffered from posttraumatic stress disorder (PTSD). Improvements in emotional regulation (emotional dysregulation is a central symptom in PTSD) accompanied improvements in PTSD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced frontostriatal connectivity in responders might explain the improvement in the binge/purge behaviors. Recently, a case series suggested that rTMS targeting the DMPFC could be helpful in treating people with comorbid eating disorders and post‐traumatic stress disorders (Woodside et al, ). These studies strongly suggest the interest of further work targeting the DMPFC in BN.…”
Section: Discussionmentioning
confidence: 99%